MRI of Autistic Brain Structure and Function - Sun, PhD, Yanping; Albert, PhD, Mitchell S. (North American Journal of Medicine and Science, 2009)
Autism is a complex development disorder defined by particular behaviors, with symptoms generally seen in three areas: deficient sociability, rigid behavior, and impaired communication skills. Early neuroimaging research focused on identifying anatomical differences between the brains of autistic versus non-autistic individuals. More recent work has emphasized the identification of functional brain areas involved in specific cognitive and social behaviors. Over the past decade, magnetic resonance imaging (MRI) has played a key role in quantifying characteristics of brain structures that possibly play roles in autism. MRI has proven extremely successful in providing functional information about brain activation and the functional connectivity of different brain regions, information that may help shed light on the neurophysiological complexities of autism etiology. [N A J Med Sci. 2009;2(2):44-47.]